Cancer-Related Psychological Distress in Lymphoma Survivor: An Italian Cross-Sectional Study - Agostinelli, Giulia; Muzzatti, Barbara; Serpentini, Samantha; Spina, Michele; Annunziata, Maria Antonietta (Frontiers in Psychology, 2022)
Cancer is becoming a chronic disease and the number of cancer survivors continues to increase. Lymphoma survivors are also increasing in numbers and anxiety and depression are among the consequences they face. The current study aimed to explore psychological distress in a sample of 212 lymphoma survivors. Information through a socio-demographic schedule and the compilation of questionnaires to assess anxiety, depression, quality of life and impact of cancer of lymphoma survivors was collected and analyzed. In the sample examined, 17% of lymphoma survivors were anxiety caseness, 12.3% depression caseness and of these 8% presented concomitant anxiety depression. This study identified some variables associated with psychological distress in lymphoma survivors: female sex; living as a couple; a diagnosis of Hodgkin lymphoma; systematic treatment and/or radiotherapy; sleep disorders; no regular physical activity; and present or past use of psychiatric drugs. Our cross-sectional study results suggest that some of the variables investigated may be useful in identifying lymphoma survivors who are more likely to report psychological distress. It is important to monitor psychological distress along the entire trajectory of survivorship in order to identify early the presence of anxiety and depression and provide timely psychological support.